IbM-Pelatihan Teknik Penulisan Parafrase Untuk Skripsi Mahasiswa Sebagai Upaya Menghindari Plagiarisme - Widya Ais Sahla; Nurul Mukhlisah; Julkawait Julkawait; Rusman Irwansyah (Politeknik Negeri Banjarmasin, 2019)
The issue of plagiarism is one of the issues that gets great attention among the academic world and is our common concern. As a manufacturer of science, Higher Education has a big responsibility to provide education and socialization related to the prevention of plagiarism. The initial conditions of our partners (students of the Islamic Economics Study Program, Faculty of Islamic Studies, Kalimantan Islamic University, Syeh Muhammad Arsyad Al-Banjari), are having difficulties in avoiding the culture of copy-paste in completing their academic assignments, especially in doing thesis. Most students still do not understand the term plagiarism and how to avoid it. After going through community service activities under the title